Total marrow irradiation reduces organ damage and enhances tissue repair with the potential to increase the targeted dose of bone marrow in both young and old mice - Lim, Ji Eun; Sargur Madabushi, Srideshikan; Vishwasrao, Paresh; Song, Joo Y.; Abdelhamid, Amr M. H.; Ghimire, Hemendra; Vanishree, V. L.; Lamba, Jatinder K.; Dandapani, Savita; Salhotra, Amandeep; Lemecha, Mengistu; Pierini, Antonio; et al. (Frontiers in Oncology, 2022)
Total body irradiation (TBI) is a commonly used conditioning regimen for hematopoietic stem cell transplant (HCT), but dose heterogeneity and long-term organ toxicity pose significant challenges. Total marrow irradiation (TMI), an evolving radiation preconditioning regimen for HCT can overcome the limitations of TBI by delivering the prescribed dose targeted to the bone marrow (BM) while sparing organs at risk. Recently, our group demonstrated that TMI up to 20 Gy in relapsed/refractory AML patients was feasible and efficacious, significantly improving 2-year overall survival compared to the standard treatment. Whether such dose escalation is feasible in elderly patients, and how the organ toxicity profile changes when switching to TMI in patients of all ages are critical questions that need to be addressed. We used our recently developed 3D image-guided preclinical TMI model and evaluated the radiation damage and its repair in key dose-limiting organs in young (~8 weeks) and old (~90 weeks) mice undergoing congenic bone marrow transplant (BMT). Engraftment was similar in both TMI and TBI-treated young and old mice. Dose escalation using TMI (12 to 16 Gy in two fractions) was well tolerated in mice of both age groups (90% survival ~12 Weeks post-BMT). In contrast, TBI at the higher dose of 16 Gy was particularly lethal in younger mice (0% survival ~2 weeks post-BMT) while old mice showed much more tolerance (75% survival ~13 weeks post-BMT) suggesting higher radio-resistance in aged organs. Histopathology confirmed worse acute and chronic organ damage in mice treated with TBI than TMI. As the damage was alleviated, the repair processes were augmented in the TMI-treated mice over TBI as measured by average villus height and a reduced ratio of relative mRNA levels of amphiregulin/ epidermal growth factor (areg/egf). These findings suggest that organ sparing using TMI does not limit donor engraftment but significantly reduces normal tissue damage and preserves repair capacity with the potential for dose escalation in elderly patients.